Rancang Bangun Sistem Informasi Manajemen Aset Berbasis Mobile Web di SMP-SMA Olahraga Negeri Sriwijaya Sumatera Selatan - Ichsan, Muhammad; Damayanti, Nita Rosa; Ariandi, Muhamad; Ulfa, Maria (Jurnal Ilmiah Matrik, 2024)
Abstract : This research is motivated by the lack of maximum service, in a government agency there needs to be asset management activities as one of the activities that handles the problem of procuring types of assets to support the operational needs of national and political unitary bodies. The aim of this research is to design and build a web-based asset management information system at Sriwijaya State Sports Middle School, South Sumatra to be able to assist goods administrators in processing data, making it easier to search for goods data, recording and reporting. The type of research used is qualitative research and the software design method used in this research is waterfall. The data collection method used is the interview method, while the testing method used is black box. It is hoped that the results of this research will provide an asset management information system website that can be accessed by management staff, utilize regional property and can connect directly with property management so that they can manage asset management data better in the future. The conclusion of this research makes it easier to process asset management data and create reports. Abstrak : Sekertariat Daerah adalah institusi atau organisasi yang membantu Bupati dalam penyusunan kebijakan dan pengoordinasian administrasi terhadap pelaksanaan tugas Perangkat Daerah serta pelayanan administratif. Masyarakat tidak hanya memperhatikan kuantitas saja, tetapi juga kualitas. Sama halnya dengan instansi atau organisasi lainnya. Salah satu cara yang dapat dilakukan adalah dengan melakukan Audit Teknologi Informasi dengan menggunakan Framework COBIT 5. Dengan mengikuti tahapan serta kriteria yang telah ditetapkan oleh COBIT. Tahapan demi tahapan tersebut akan menghasilkan sebuah parameter tingkat kelola suatu teknologi informasi yang disebut Capability Level. Dimana parameter tersebut nantinya akan digunakan sebagai tolak ukur dengan membandingkan dengan target yang ingin dicapai. Selisih antara target yang ingin dicapai dengan keadaan saat ini disebut dengan Gap Analisis.